A Review of De Novo Programming - Mega Yumia; Febrianto Afli (Journal Electrical and Computer Experiences, 2023)
The article explores some of the developments in de novo programming. The research that has been chosen for discussion may be obtained on Google Scholar by searching for "De Novo Optimalization"; it is not a case study. Integrating uncertainty into De Novo programming through the addition of fuzzy functions and strategies for its resolution is one of the primary research development goals for the discipline.